Administração provincial e governabilidade no império brasileiro: um estudo a partir do perfil de recrutamento e da comunicação política dos presidentes de Província do Rio Grande do Sul (1845-1889) - Both, Amanda Chiamenti (2020)
In 1823, shortly after Brazil’s emancipation, the law that outlined the architecture of the provincial government was approved and instituted that in each province there would be a President, who would be appointed and removable by the Emperor's. Throughout this work, we supported the thesis that provincial presidents were extremely relevant pieces in the Imperial world because they represent the institutional element responsible for connecting provinces to the central government, along with their administrative actions regarding provincial issues. Specifically, we seek to identify the administrative practices that conformed the way to govern the province through the analysis of the political communications. The investigation favored the province of Rio Grande do Sul, in the period between 1845, after the supplanting of the Farroupilha’ uprising, and 1889. To investigate this conjecture, we carried out an analysis of the political power structure at provincial sphere, paying especial attention to the legislation that regulated the president's performance. We found that their competencies had focused mainly on the supervision of organs and institutions linked to the State, and on the information collection regarding its functioning. Furthermore, we profiled the individuals named for the positions. We verified that such choice was direct towards politicians with a law degree, and the other criteria varied accordingly the current conjecture. We also investigated the different forms of political communication used by the presidents, aiming to know both the main interlocutors and the other people who guided these communications. We observed that it was through constant dialogue with the provincial authorities that the president obtained the means necessary for the governance of this territorial unity. The performance of these functions over time conformed administrative practices that were used by the position holders, and indeed the most important function was the assembly of communication circuits that allowed the collection of information about the province and its inhabitants. The president passed some of this information to the central government, that guided the resolutions to be taken when necessary. These data were also taken in to account to decide when and how to intervene. Therefore, the information exchange carried out through these paths was one of the main ways to shorten the distances of the vast Brazilian’s empire.